Paratriathlon race performance in high-level athletes with visual impairments: A retrospective analysis - Lima, G. B.; Kons, R. L.; Detanico, D.; Fischer, G. (American Journal of Physical Medicine & Rehabilitation, 2023)
OBJECTIVES: The aim of this study was to compare time-trial performances in elite para-triathlon athletes, according to visual classes, sex, and medal distribution. DESIGN: The data were acquired from official books on Para Triathlon World Cups (2018-2020). The sample included 150 athletes with visual impairment (VI), in classes: PTVI1, PTVI2, and PTVI3. One-way analysis of variance, the student t-test, and Chi-squared were used to compare the performance variables and association between VI classes and distribution of medals within different VI classes. RESULTS: Sex comparisons demonstrated better performance for male compared to females (p < .05). In the sex-specific analysis, only cycling velocity was higher for female, being lower for PTVI1 compared to PTVI3 (p = .012). In VI class results, the first transition time was higher for PTVI1 compared to PTVI2 (p = .050) and PTVI3 (p = .027), and in the second transition, higher for PTVI1 compared to PTVI2 (p = .001). The Chi-squared test showed a higher percentage of gold medals for PTVI3 athletes considering the whole group (p = .050). CONCLUSIONS: These results indicate that male have better performance than female. PTVI1 female athletes showed lower cycling velocity compared to PTVI3. Considering both male and female groups, blind athletes presented higher transition times and a lower percentage of medals.